Oxygen vacancy associated single-electron transfer for photofixation of CO2 to long-chain chemicals - Shichuan Chen (Nature Portfolio, 2019)
The photofixation and utilization of CO2 is considered to be a clean and green way to produce high-value-added commodity chemicals, but production of long chain chemicals through this process remains a challenge. Here, the authors develop a practical way for the photofixation of CO2 to long-chain chemicals via defect engineering.